HIV, syphilis, and viral hepatitis among Latin American indigenous peoples and Afro-descendants: a systematic review - Nancy K. Russell; Kevin Nazar; Sandra del Pino; Monica Alonso Gonzalez; Ximena P. Díaz Bermúdez; Giovanni Ravasi (Pan American Health Organization, 2019)
Objective. To identify and summarize existing literature on the burden of HIV, sexually transmitted infections (STIs), and viral hepatitis (VH) in indigenous peoples and Afro-descendants in Latin America to provide a broad panorama of the quantitative data available and highlight problematic data gaps. Methods. Published and grey literature were systematically reviewed to identify documents published in English, Spanish, or Portuguese with data collected between January 2000 and April 2016 on HIV, STI, and VH disease burden among indigenous peoples and Afro-descendants in 17 Latin American countries. Results. Sixty-two documents from 12 countries were found. HIV prevalence was generally low (< 1%) but pockets of high prevalence (> 5%) were noted in some indigenous communities in Venezuela (Warao) (9.6%), Peru (Chayahuita) (7.5%), and Colombia (Wayuu females) (7.0%). High active syphilis prevalence (> 5%) was seen in some indigenous communities in Paraguay (11.6% and 9.7%) and Peru (Chayahuita) (6.3%). High endemicity (> 8%) of hepatitis B was found in some indigenous peoples in Mexico (Huichol) (9.4%) and Venezuela (Yanomami: 14.3%; Japreira: 29.5%) and among Afro-descendant quilombola populations in Brazil (Frechal: 12.5%; Furnas do Dionísio: 8.4% in 2008, 9.2% in 2003). Conclusions. The gaps in existing data on the burden of HIV, STIs, and VH in indigenous peoples and Afro-descendants in Latin America highlight the need to 1) improve national surveillance, by systematically collecting and analyzing ethnicity variables, and implementing integrated biobehavioral studies using robust methodologies and culturally sensitive strategies; 2) develop a region-wide response policy that considers the needs of indigenous peoples and Afro-descendants; and 3) implement an intercultural approach to health and service delivery to eliminate health access barriers and improve health outcomes for these populations.